Decreased Perifoveal Sensitivity Detected by Microperimetry in Patients Using Hydroxychloroquine and without Visual Field and Fundoscopic Anomalies - A. Molina-Martín; D. P. Piñero; R. J. Pérez-Cambrodí (Journal of Ophthalmology)
Purpose. To evaluate the usefulness of microperimetry in the early detection of the ocular anomalies associated with the use of hydroxychloroquine. Methods. Prospective comparative case series study comprising 14 healthy eyes of 7 patients (group A) and 14 eyes of 7 patients under treatment with hydroxychloroquine for the treatment of rheumatologic diseases and without fundoscopic or perimetric anomalies (group B). A comprehensive ophthalmological examination including microperimetry (MP) and spectral-domain optical coherence tomography was performed in both groups. Results. No significant differences were found in mean MP foveal sensitivity between groups P=0.18. However, mean MP overall sensitivity was significantly higher in group A (29.05±0.57 dB versus group B, 26.05±2.75 dB; P<0.001). Significantly higher sensitivity values were obtained in group A in comparison to group B for the three eccentric loci evaluated P<0.001. Conclusion. Microperimetry seems to be a useful tool for the early detection of retinal damage in patients treated with hydroxychloroquine.